Pembiasaan Istighosah Dalam Pembentukan Kecerdasan Spiritual Santri - Sunardi, Sunardi; Fathoni, Muchlis Tri; Munfarida , Isah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
One of the aims of istigosah carried out at the Al Urwatul Wutsqo Islamic Boarding School in Jombang. Therefore, this research examines in depth how the istighosah activities of male students are carried out at the Islamic Boarding School in improving the intelligence of male students, as well as how the istighosah activities of male students at the Islamic Boarding School improve their intelligence. The data collection techniques used were interviews, observations, and documentation. Meanwhile, data analysis used data reduction, data presentation, verification and conclusions. The results and conclusions of this study are that the implementation of istighosah activities for male students at the Al-Urwatul Wutsqo Islamic Boarding School in Diwek, Jombang is as follows: First, the implementation of compulsory istigosah for students who have been initiated, even though it can be done by people who have not been initiated. Second, the timing of Istigosah is only at the time determined by a Mursyid of the Tariqa. Third, the characteristic of istighosah in this Islamic Boarding School is not the same as istigosah in other Islamic Boarding Schools. The improvement of the spiritual intelligence of male students at the Al-Urwatul Wutsqo Islamic Boarding School in Diwek, Jombang is carried out in several ways as follows: First, students are educated to feel the presence of Allah in their lives. Second, students are educated to perform dhikr and prayer. Third, students' quality of patience is improved. Fourth, students have high empathy. Fifth, students have a big heart.